Environmental factors associated with childhood eczema: Findings from a national web-based survey - Mari Sasaki; Koichi Yoshida; Yuichi Adachi; Mayumi Furukawa; Toshiko Itazawa; Hiroshi Odajima; Hirohisa Saito; Michihiro Hide; Akira Akasawa (Allergology International, 2016)
Background: Genetic and environmental factors are known to be related to the development of childhood eczema. Our aim was to assess the environmental factors associated with the prevalence of eczema among children using a web-based survey. Methods: In June 2012, we conducted a nation-wide web-based survey to identify the prevalence and characteristics of allergic diseases among Japanese children. The prevalence of allergic diseases including eczema was assessed using the International Study of Asthma and Allergies in Childhood core questionnaire. The associations between eczema prevalence and environmental factors, as well as those between background characteristics and comorbid allergic diseases among 6–12 year old children were assessed. Results: A total of 28,348 children were included in the analysis. The prevalence of current eczema was 13.0%. Current eczema was significantly associated with a higher prevalence of wheeze, rhinitis, and food allergy. In multiple logistic regression models, birth during autumn (aOR: 1.18 95%CI: 1.06–1.31) or winter (aOR: 1.21 95%CI: 1.08–1.34), duration of exclusive breastfeeding for at least 6 months (aOR: 1.14 95%CI: 1.06–1.23), and ownership of a pet from infancy (aOR: 2.61 95%CI: 1.68–4.07) were also associated with a higher prevalence of eczema. The prevalence was lower in those with a high annual household income (aOR: 0.90 95%CI: 0.81–0.99) and 2 or more siblings (aOR: 0.86 95%CI: 0.76–0.97). Conclusions: Duration of breastfeeding, season of birth, pet ownership, household income, and the number of siblings were associated with the prevalence of childhood eczema in a nationwide web survey.